Upper extremity deep vein thrombosis in an informal porter - Dewi S. Soemarko; Herlinah Herlinah (Universa Medicina, 2020)
BackgroundUpper extremity deep vein thrombosis (UEDVT) is a rare condition, in which job-related arm movements and repetitive, forceful or overhead arm activities have been recognized as the predisposing factor for this condition. UEDVT can occur among informal porters. This report describes a case of UEDVT in an informal porter due to manual lifting of heavy goods and reviews the literature for occupational reports of this condition.Case descriptionA 35-year-old male informal porter presented with marked swelling, pain, and numbness of his right arm 3 days after a prolonged episode of lifting heavy goods. A Doppler ultrasound showed thrombosis in the right subclavian and axillary veins and laboratory tests found elevated D-dimer. Patient was diagnosed as having axillo-subclavian thrombosis and treated with low molecular-weight heparin. One month after the last follow-up, patient returned to work with modified capacity and after 3 months of return to work, patient was able to resume his regular duties without impairment or disability.ConclusionThe occupation of informal porter should be considered a risk factor for upper extremity deep vein thrombosis (UEDVT), thus the occupational medicine physician should be aware of this condition in the context of manual workers. Detailed occupational history to aid the diagnosis and future risk assessment are needed, and education for preventing UEDVT should be provided to porters.